The eye of Moloch - Beck, Glenn (Threshold Editions-Mercury Radio Arts, 2013)
The battle lines in this bitter rivalry are as old as civilization itself: On one side, an unlikely band of ordinary Americans ready to make their last stand in defense of self-rule, freedom, and liberty, and on the other, an elite cabal of self-styled tyrants who believe that unlimited power should be wielded only by the chosen few. That group, led by an aging, trillionaire puppet-master named Aaron Doyle, will stop at nothing to destroy the myth that man is capable of ruling himself.